POTENSI DAN PROYEKSI EKONOMI MAKRO KOTA TANGERANG - Lestari Agusalim (MediaTrend, 2016)
This study aims to analyse the potency and make a projection of the economy of Tangerang Municipality from 2014 to 2018. By doing so, the local government of Tangerang can use such information to formulate the appropriate policies to foster inclusive economic growth. This study is essential as Tangerang Municipality experienced a slow down in economic growth in 2014 compared to the previous year. This study uses quantitative methods namely Location Quotient (LQ) analysis, to identify leading sectors of the economy, and Least Squares Method, to make a projection of the economy. In addition, descriptive analysis is also used to briefly interpret the quantitative data and formulate policy recommendations. The results show that: (1) the leading sectors of Tangerang Municipality are manufacturing industry sector, transportation and warehousing sector, information and communication sector, and business services sector; (2) the projection analysis showed that in 2018, based on constant price and current price RGDP, Tangerang Municipality will experience positive economic growth. This will also be true for per capita RGDP. Moreover, inflation and open unemployment rate will decline.